Failure Precursors and Failure Mechanisms in Hierarchically Patterned Paper Sheets in Tensile and Creep Loading - Poornajar, Mahshid; Mäkinen, Tero; Hosseini, Seyyed Ahmad; Moretti, Paolo; Alava, Mikko; Zaiser, Michael (Physical Review Applied, 2023)
Quasibrittle materials endowed with (statistically) self-similar hierarchical microstructures show distinct failure patterns that deviate from the standard scenario of damage accumulation followed by crack nucleation and growth. Here we study the failure of paper sheets with hierarchical slice patterns as well as nonhierarchical and unpatterned reference samples, considering both uncracked samples and samples containing a macroscopic crack. Failure is studied under displacement-controlled tensile loading as well as under creep conditions. Acoustic emission records and surface strain patterns are recorded alongside stress-strain and creep curves. The measurements demonstrate that hierarchical patterning efficiently mitigates against strain localization and crack propagation. In tensile loading, this results in a significantly increased residual strength of cracked samples. Under creep conditions, for a given range of lifetimes, hierarchically patterned samples are found to sustain larger creep strains at higher stress levels; their creep curves show unusual behavior characterized by multiple creep rate minima due to the repeated arrest of emergent localization bands.
CRIS-Team Scopus Importer:2023-09-29